New mechanistic insights into hepatoprotective activity of milk thistle and chicory quantified extract: The role of hepatic Farnesoid-X activated receptors - Azadeh Khalili; Parviz Fallah; Seyed Ali Hashemi; Mohammad Mahdi Ahmadian-Attari; Vahid Jamshidi; Roham Mazloom; Leila Beikzadeh; Gholamreza Bayat (Mashhad University of Medical Sciences, 2021)
Objective: Farnesoid-X-activated receptors (FXR) are key modulators of liver regeneration. Milk thistle and Chicory are known as potent protective remedies in several liver disorders. The objective of this work was to examine the role of FXR in the hepato-healing properties of milk thistle (MTE) and chicory extracts (CE) in a rat model of acetaminophen-induced hepatotoxicity. Materials and Methods: Male Wistar rats were randomly divided into seven groups including control, vehicle, acetaminophen (500 mg/kg/day, oral), acetaminophen plus oral MTE 200 and 400 mg/kg/day, and acetaminophen plus oral CE 500 and 1000 /kg/day for 28 days. Liver function and histology as well as the pattern of hepatic FXR expression were assessed after 4 weeks. Results: Administration of acetaminophen was associated with a significant elevation of liver transaminase along with the architectural injuries. In contrast, chronic concomitant administration of both MTE and CE significantly restored the liver function and structural abnormality. The main molecular findings of the study revealed that the lower doses of both MTE and CE led to a marked upregulation of hepatic FXR expression. Conclusion: Discovery of the involvement of the nuclear modulating pathways in hepatoprotective activity of the extracts, providesa new mechanistic insight which needs further investigations.